Environmental Law Enforcement Against Drug Abuse Against Children - Pradana, Azaria Hegar (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
Children are the hope of the nation. As the next generation, continuous guidance and protection are needed for the sake of survival, growth and physical, mental, social development as well as protection from all possibilities that will endanger them (children) and in the future. Narcotics and other illegal drugs are one of the triggers for the destruction of children. Children are often the target of drug dealers, because children are still unstable, easily influenced so that they have the potential to be trapped in the abuse of illegal drugs such as narcotics. Children as drug abusers are only victims. So it is not appropriate for the state to give punishment by considering child abusers the same as adult criminals (dealers) who are real. In the juvenile criminal justice system in Indonesia, children as drug abusers still undergo the trial process. The trial process is to hold children accountable. Even though they are undergoing the trial process, children should still receive protection. The consideration of child drug abusers getting protection, because it is believed that child drug abuse does not entirely come from the child, but rather from the influence of the surrounding environment. Rehabilitation is a process of recovering someone from drug use disorders, this recovery is short-term or long-term. The goal is to restore the individual's function in society. Victims of drug abuse in society lately tend to increase not only in groups of people who are able, but have also spread to the less able community both in cities and villages.